(untitled) (LEGAL DIALOGICA, 2025)
This research aims to provide proposals for the concept and analysis of asset forfeiture without punishment in corruption crimes in Indonesia. The type of research used is normative legal research. The legal research method emphasizes the study of legal problems on the issue of norms. This approach will focus on examining legal reality from the perspective of the legal substance that regulates and is still in draft. The results of the study indicate that (1) The concept of asset forfeiture in Indonesian legislation can be found in the Criminal Code, Criminal Procedure Code, Anti-Corruption Law, Anti-Money Laundering Law, and/or other sectoral laws. However, the law does not explicitly regulate asset forfeiture without punishment, but regulates asset forfeiture through criminal proceedings. Therefore, it is very necessary to pass the Asset Forfeiture Bill which contains the concept of Non-Conviction Based Asset Forfeiture as mandated by UNCAC 2003. This is because the existing laws and regulations have not comprehensively and in detail regulated the seizure of assets resulting from criminal acts, so there are still many loopholes that need to be refined. (2) This Asset Forfeiture Bill has a very clear purpose, but of course in its presentation there are still gaps that can be criticized and debated, none other than all of that is intended for the common good, both the community as a subject subject to the law and also law enforcement officials (APH) as implementers of the rules made. In this case, the Draft Law on Asset Forfeiture is in line with human rights as contained in the 1945 Constitution and Law Number 39 of 1999 concerning Human Rights. This is inherent in the provision of restrictions on asset forfeiture contained in Article 14 Paragraph 1 of the Draft Law on Asset Forfeiture Abstrak Penelitian ini bertujuan untuk memberikan usulan terhadap konsep dan anilisis perampasan aset tanpa pemidanaan dalam tindak pidana korupsi di Indonesia. Jenis penelitian yang digunakan adalah penelitian hukum normatif. Metode penelitian hukum menitikberatkan pengkajian masalah hukum pada persoalan norma. Pendekatan ini akan fokus menelaah kenyataan hukum dari kacamata substansi hukum yang mengatur maupun yang masih dalam rancangan. Hasil penelitian menujukkan bahwa (1) Konsep perampasan aset dalam perundang-undangan di Indonesia dapat ditemukan dalam KUHP, KUHAP, UU Tipikor, UU TPPU, dan/atau UU sektoral lainnya. Namun undang-undang a quo tidak secara tegas mengatur perampasan aset tanpa pemidanaan, tetapi mengatur perampasan aset melalui proses pidana. Oleh karena itu sangat diperlukan pengesahan RUU Perampasan Aset yang memuat konsep Non-Conviction Based Asset Forfeiture sebagaimana diamanatkan oleh UNCAC 2003. Hal ini dikarenakan peraturan perundang-undangan yang ada belum secara komprehensif dan rinci mengatur tentang perampasan aset hasil tindak pidana, sehingga masih terdapat banyak kekurangan (loophole) yang perlu disempurnakan. (2) RUU Perampasan Aset ini memiliki tujuan yang sangat jelas, namun tentu dalam penyajiannya masih saja ada celah yang dapat dikritik dan diperdebatkan, tidak lain dan tidak bukan semua itu dimaksudkan untuk kebaikan bersama, baik masyarakat sebagai subjek yang dikenai hukum dan juga aparat penegak hukum (APH) sebagai pelaksana dari aturan yang dibuat tersebut. Dalam hal ini Rancangan Undang-Undang (RUU) Perampasan Aset telah sejalan dengan hak asasi manusi (HAM) sebagaimana yang terdapat dalam UUD NRI 1945 maupun Undang-Undang Nomor 39 Tahun 1999 Tentang Hak Asasi Manusia (HAM). Hal tersebut inheren dengan ketentuan pembatasan perampasan aset yang tertuang dalam Pasal 14 Ayat 1 Rancangan Undang-Undang (RUU) Perampasan Aset.